Host behavior alters spiny lobster–viral disease dynamics: a simulation study - Thomas W. Dolan; Mark J. Butler IV; Jeffrey D. Shields (Ecology, 2014)
Social behavior confers numerous benefits to animals but also risks, among them an increase in the spread of pathogenic diseases. We examined the trade‐off between risk of predation and disease transmission under different scenarios of host spatial structure and disease avoidance behavior using a spatially explicit, individual‐based model of the host–pathogen interaction between juvenile Caribbean spiny lobster ( Panulirus argus ) and Panulirus argus Virus 1 (PaV1). Spiny lobsters are normally social but modify their behavior to avoid diseased conspecifics, a potentially effective means of reducing transmission but one rarely observed in the wild. We found that without lobster avoidance of diseased conspecifics, viral outbreaks grew in intensity and duration in simulations until the virus was maintained continuously at unrealistically high levels. However, when we invoked disease avoidance at empirically observed levels, the intensity and duration of outbreaks was reduced and the disease extirpated within five years. Increased lobster (host) spatial aggregation mimicking that which occurs when sponge shelters for lobsters are diminished by harmful algal blooms, did not significantly increase PaV1 transmission or persistence in lobster populations. On the contrary, behavioral aversion of diseased conspecifics effectively reduced viral prevalence, even when shelters were limited, which reduced shelter availability for all lobsters but increased predation, especially of infected lobsters. Therefore, avoidance of diseased conspecifics selects against transmission by contact, promotes alternative modes of transmission, and results in a more resilient host–pathogen system.

Sperm economy and limitation in spiny lobsters - A. B. MacDiarmid; Mark J. Butler IV (Behavioral Ecology and Sociobiology, 1999)